1990
DOI: 10.1172/jci114725
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin potentiates prestimulated acid secretion and mobilizes intracellular calcium in rabbit parietal cells.

Abstract: The effects of aspirin on gastric acid secretion were studied in isolated rabbit parietal cells (PC). Aspirin (i0-5 M) potentiated histamine-, dibutyryl cyclic AMP (dbcAMP)-, forskolin-and 3-isobutyl-1-methylxanthine-stimulated acid secretion without affecting basal acid secretion. Augmentation of secretagogue-stimulated acid secretion by aspirin was dependent on calcium (Ca2") since potentiation was blocked by removal of extracellular Ca2+ ([Ca2+1.) or addition of the calcium antagonist lanthanum chloride. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…respect to possible alternative mechanisms of airway epithelial HCO 3 Ϫ secretion, we failed to detect evidence of an anion exchanger that might be regulated by CFTR on the apical membrane of airway epithelium (22) (26). Taken together, these data indicate that CF cultures lack the capacity to secrete HCO 3 Ϫ to match H ϩ ,K ϩ -ATPase-mediated proton secretion into ASL under basal and cAMP-stimulated conditions, resulting in ''hyperacidification'' of ASL.…”
Section: Discussionmentioning
confidence: 70%
“…respect to possible alternative mechanisms of airway epithelial HCO 3 Ϫ secretion, we failed to detect evidence of an anion exchanger that might be regulated by CFTR on the apical membrane of airway epithelium (22) (26). Taken together, these data indicate that CF cultures lack the capacity to secrete HCO 3 Ϫ to match H ϩ ,K ϩ -ATPase-mediated proton secretion into ASL under basal and cAMP-stimulated conditions, resulting in ''hyperacidification'' of ASL.…”
Section: Discussionmentioning
confidence: 70%
“…For example, trafficking of aquaporin-2 to the apical membrane of collecting duct principal cells in response to vasopressin is dependent on intracellular calcium release from ryanodine-sensitive stores (7). Intracellular calcium also regulates H ϩ -K ϩ -ATPase in both the stomach and the colon (20,26,28,39), 10% CO 2 -dependent stimulation of CCD H ϩ -K ϩ -ATPase (52), and collecting duct H ϩ -ATPase stimulation by metabolic acidosis (38,43). Finally, intracellular calcium plays a role in SNARE-protein-mediated vesicle fusion with plasma membranes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Different in vivo studies carried out in humans have demonstrated that both acetylsalicylic acid and indomethacin are able to increase the basal rate of acid formation (8,12,21,29) and to potentiate acid secretion stimulated by histamine (21,29). Furthermore, in vitro studies carried out in isolated rabbit fundic glands (48), in preparations of rat gastric mucosa (41), or in isolated rabbit parietal cells (27,28,37) have demonstrated that micromolar concentrations of aspirin and other NSAIDs, like indomethacin, piroxicam, and naproxen, may potentiate gastric acid secretion stimulated by histamine, dibutyryl cAMP, or forskolin without affecting the basal rate of acid formation. The biochemical mechanism of this potentiation is not well established.…”
mentioning
confidence: 99%